A detailed analysis of the current status of intestinal transplantation in the middle east. Issue 2 (April 2020) - Nikeghbalian, Saman; Arasteh, Peyman; Nikoupour, Hamed
Abstract : Purpose of review: Intestinal transplantations are among the most complex transplantations, which are performed in few centers in the world. When patients develop intestinal failure, different treatment modalities including parenteral nutrition, autologous gastrointestinal tract reconstructive surgery, and intestinal transplantations are considered. The Middle East is a region where reports on intestinal failures and intestinal transplantations are mainly lacking. In the present review, we highlighted the status of intestinal transplantations in the Middle East and focused on existing reports from this region. Recent findings: Very few countries in the Middle East have the facilities for home parenteral nutrition and only two countries including Iran and Turkey perform intestinal transplantations in the region. With advances in intestinal rehabilitation units and development of autologous gastrointestinal tract reconstructive surgery, some centers have been able to reduce the number of patients in need of intestinal transplantations. Summary: An overview of the condition of intestinal transplantations in the Middle East shows that the issue of intestinal failure and the treatment facilities still remain an unsolved problem. Although there exists a high need for intestinal transplantation, advances in reconstructive surgeries and the development of parenteral nutrition in this region can significantly reduce the need for intestinal transplantations among patients with intestinal failure.